Swimming against the European current - Hornek, Jakub (Journal of comparative politics, 2025)
Czechia represents an outlying case of a settlement structure where more than half of the municipalities have under 500 inhabitants but account for only eight percent of the country’s total population. This study analyses the factors behind variability in the amount of liabilities (as a possible indicator of development) in the balance sheets of the more than three thousand smallest Czech municipalities. The results show that the amount of liabilities is strongly positively associated with municipality size, which also explains a negative effect of voter turnout, which decreases with growing local population in the Czech context. Besides the effect of size, there are also constant (albeit much weaker) effects of geographical factors, with higher amounts of liabilities found in larger municipalities in closer vicinity to regional centres and outside structurally disadvantaged regions. This suggests the problem of an ineffective state of local governments in Czechia. Thus, the smallest municipalities with low levels of competitiveness (i.e. citizens’ low willingness to join their local governments) found in peripheral regions or in the peripheries of more developed regions are faced with major developmental problems. An increasing number of municipalities are stagnating due to insufficient funds for their development.
Keywords: competitiveness; Konkurenca (ekonomija); liabilities; local governments; Lokalna samouprava; municipal reform; Občine; small municipalities; sustainable development; Trajnostni razvoj